2010
DOI: 10.2747/0272-3646.31.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Climate Change Across Wisconsin From 1950 to 2006

Abstract: Trends in meteorological and ecological variables were calculated across the state of Wisconsin from 1950 to 2006 to quantify recent patterns of climate change. In summary, annual average nighttime low temperatures have increased by 0.6 to 2.2º C, whereas the annual average daytime high temperatures have warmed by 0.3 to 0.6º C. Annual average precipitation has increased by 50-100 mm in the central and southern portions of the state, about a 10-15% increase, while precipitation across the far northern portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(110 citation statements)
references
References 28 publications
3
106
1
Order By: Relevance
“…These data are also similar to results from other regional studies. Measurements from Wisconsin weather stations between 1950 and 2006 show that minimum (low) temperatures have increased 1.1 to 4.0 °F (0.6 to 2.2 °C) across the state (Kucharik et al 2010a). This is greater than the increase in maximum temperatures, which have risen 0.5 to 1.1 °F (0.3 to 0.6 °C) during the same time period.…”
Section: Trends In Temperature and Precipitation (1901-2011) Temperaturementioning
confidence: 81%
See 2 more Smart Citations
“…These data are also similar to results from other regional studies. Measurements from Wisconsin weather stations between 1950 and 2006 show that minimum (low) temperatures have increased 1.1 to 4.0 °F (0.6 to 2.2 °C) across the state (Kucharik et al 2010a). This is greater than the increase in maximum temperatures, which have risen 0.5 to 1.1 °F (0.3 to 0.6 °C) during the same time period.…”
Section: Trends In Temperature and Precipitation (1901-2011) Temperaturementioning
confidence: 81%
“…°C) are becoming less frequent in Wisconsin. There were 9.5 fewer such days statewide and 20 fewer such days in the northwest portion of the state between 1950 and 2006 (Kucharik et al 2010a). A study across the entire Midwest region found that intense cold waves (4-day durations of temperatures below a 1-in-5-year recurrence threshold) have been less frequent over the past 1 years, but there has not been a clear trend across the 20th century (Perera et al 2012).…”
Section: Temperature Extremesmentioning
confidence: 99%
See 1 more Smart Citation
“…Overuse of pesticides, fertilizers, and manure, along with increased flashiness of runoff from heavy rainfall events, have amplified concern about freshwater quality because people are sometimes unable to swim or boat in the lakes. Climate change has altered hydrological flows (Motew and Kucharik 2013), lengthened the growing season, increased the occurrence of extreme rainfall events (Kucharik et al 2010), and altered plant and animal phenology (Bradley et al 1999). Invasions of nuisance animals and plants also have ongoing effects on ecosystem services in the Yahara watershed (Carpenter et al 2007).…”
Section: The Yahara Watershedmentioning
confidence: 99%
“…These authors emphasized the importance of different drivers of change in different places and their variable impact on ecological structures and functions. The need for fit-for-place design solutions to manage urban climates has been recognized [14] and geographers are not just concerned about global warming, they are concerned about the local effects of climate change, such as patterns of climate change across Wisconsin [15].…”
Section: The Uniqueness Of Placesmentioning
confidence: 99%